Specificity of mismatch repair following transformation of Saccharomyces cerevisiae with heteroduplex plasmid DNA. - Bishop, D K (1989)
A method is described for genetic detection of mismatch repair products following transformation of Saccharomyces cerevisiae. The method is based on the detection of beta-galactosidase activity in clonal derivatives of cells transformed with heteroduplex plasmid DNA. Heteroduplex plasmid substrates were constructed by insertion of an oligonucleotide heteroduplex into the coding sequence of the Escherichia coli lacZ gene. The plasmid and oligonucleotides were designed so that one strand of the construct would code for a functional beta-galactosidase and the other strand would contain an in-frame nonsense codon. The frequencies of transformed clones containing only Lac+ cells, only Lac- cells, or a mixture of the two Lac phenotypes provided information on the efficiency of the repair reaction. With this method, plasmids carrying single-base substitution mismatches, a single-base frameshift mismatch (T/delta), or a 3-base-pair substitution mismatch (TGA/GAA) were tested. A/C, G/T, G/A, G/G, and T/delta mismatches were repaired with significantly greater efficiencies than C/C, A/A, T/T, and TGA/GAA. T/C was repaired with an intermediate efficiency. The frequencies of products obtained with G/G, G/A, and T/delta mismatches suggested modest inequality of repair in the two possible directions. Strains carrying the repair-deficient pms1-1 mutation were also tested. The efficiencies of repair of A/C, G/T, G/G, and A/A mismatches were reduced in pms1-1 cells compared with wild-type cells. In addition, a change in repair inequality was detected when transformation of the two strains with an A/C mismatch was compared.